Idiopathic Central Pontine and Extrapontine Myelinolysis in a Child - Kamath, Madhav (J Pediatr Neurosci, 2019)
The objective of this study was to report a case of central pontine and extrapontine myelinolysis in a child, a rare neurological disorder. A diagnosis of demyelination carries important therapeutic and prognostic implications. In most cases, the diagnosis is made clinically and confirmed radiologically. Treatment should be initiated sincerely as severe cases have a dismal prognosis.